VHH characterization. Comparison of recombinant with chemically synthesized anti‐HER2 VHH. (29th August 2019) - Hartmann, Lucie; Botzanowski, Thomas; Galibert, Mathieu; Jullian, Magali; Chabrol, Eric; Zeder‐Lutz, Gabrielle; Kugler, Valérie; Stojko, Johann; Strub, Jean‐Marc; Ferry, Gilles; Frankiewicz, Lukasz; Puget, Karine; et al.
Abstract: In the continuous exploration of the VHH chemistry, biochemistry and therapeutic future use, we investigated two different production strategies of this small antibody‐like protein, using an anti‐HER2 VHH as a model. The total chemical synthesis of the 125 amino‐acid peptide was performed with reasonable yield, even if optimization will be necessary to upgrade this kind of production. In parallel, we expressed the same sequence in two different hosts: Escherichia coli and Pichia pastoris . Both productions were successful and led to a fair amount of VHHs. The integrity and conformation of the VHH were characterized by complementary mass spectrometry approaches, while surface plasmon resonance experiments were used to assess the VHH recognition capacity and affinity toward its "antigen." Using this combination of orthogonal techniques, it was possible to show that the three VHHs—whether synthetic or recombinant ones—were properly and similarly folded and recognized the "antigen" HER2 with similar affinities, in the nanomolar range. This opens a route toward further exploration of modified VHH with unnatural amino acids and subsequently, VHH‐drug conjugates.